2010
DOI: 10.2478/s11686-010-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

Gyrodactylids (Gyrodactylidae, Monogenea) infecting Oreochromis niloticus niloticus (L.) and O. mossambicus (Peters) (Cichlidae): A pan-global survey

Abstract: Gyrodactylus infections in intensively-reared populations of Nile tilapia, Oreochromis niloticus niloticus, have been associated world-wide with high mortalities of juvenile fish. In this study, 26 populations of Gyrodactylus parasitising either O. n. niloticus or Mozambique tilapia, Oreochromis mossambicus, were sampled from fourteen countries and compared with type material of Gyrodactylus cichlidarum Paperna, 1968, Gyrodactylus niloticus (syn. of G. cichlidarum) and Gyrodactylus shariffi Cone, Arthur et Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
1
24
0
3
Order By: Relevance
“…nov. are morphologically similar to those of G. cichlidarum, a PCA analysis of the morphometric data suggested that they can be separated (see García-Vásquez et al 2010). This finding was supported by a parallel molecular analysis which identified 42 nucleotide differences in the ITS regions between the two species.…”
supporting
confidence: 65%
See 4 more Smart Citations
“…nov. are morphologically similar to those of G. cichlidarum, a PCA analysis of the morphometric data suggested that they can be separated (see García-Vásquez et al 2010). This finding was supported by a parallel molecular analysis which identified 42 nucleotide differences in the ITS regions between the two species.…”
supporting
confidence: 65%
“…nov. and G. cichlidarum are subtle and although a principal components analysis (PCA) of morphometric data suggested a difference (see García-Vásquez et al 2010), their clear differentiation from each other was confirmed by the molecular study. Altogether, there are 42 differences between the ITS1 and ITS2 of G. ulinganisus sp.…”
Section: Commentsmentioning
confidence: 99%
See 3 more Smart Citations